Synthesis of 1,2-dihydroxyimino-1-phenyl-3,7-diaza-9,10-O-benzaloctane and its complexes with Co(II), Cu(II) and Ni(II) - Tas, E; Çukurovali, A (Gordon Breach Sci Publ Ltd, 1999)
A novel dioxime, 1,2 dihydroxyimino-3,7-diaza-9,10-O-benzaloctane (LH2) was prepared by reaction of 1,2-O-benzylidene-4-aza-7-aminoheptane and anti-phenylchloroglyoxime in absolute ethanol. Mononuclear complexes with a metal-ligand ratio of 1:2 were prepared with Co(II), Cu(II) and Ni(II). To elucidate the structures of the ligand and complexes, elemental analyses, IR, H-1 NMR and C-13 NMR spectral data and magnetic susceptibility measurements have been examined.
Keywords: dioxime; cobalt(II); copper(II); nickel(II); diaza macrocycle